Esophageal biopsies in NERD - a new standard? 1st die Biopsieentnahme aus dem Ösophagus bei verdacht auf NERD neuer standard? - Neumann, Helmut; Langner, C.; Vieth, M. (Verdauungskrankheiten, 2012)
Gastroesophageal reflux disease (GERD) affects up to 10% of the general population. Differentiation between erosive (ERD) and non-erosive reflux disease (NERD) is based on endoscopic data and patients complaints (mostly heartburn). Currently, there is a controversial discussion about the imperative of esophageal biopsies for diagnosis of NERD. In this review we will focus on disease aspects and histopathological alterations in NERD to finally answer the question: are esophageal biopsies in NERD the new standard?. © 2012.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett; Biopsy; ERD; Gastroesophageal reflux disease; NERD; Pathology; PPI; Proton pump inhibitor